2014
DOI: 10.1136/vr.102553
|View full text |Cite
|
Sign up to set email alerts
|

Ethics teaching in European veterinary schools: a qualitative case study

Abstract: Veterinary ethics is recognised as a relevant topic in the undergraduate veterinary curriculum. However, there appears to be no widely agreed view on which contents are best suited for veterinary ethics teaching and there is limited information on the teaching approaches adopted by veterinary schools. This paper provides an inside perspective on the diversity of veterinary ethics teaching topics, based on an in-depth analysis of three European veterinary schools: Copenhagen, Lisbon and Nottingham. The case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…7 A structured curriculum usually provides scientific evidence and ethical discussion of animal welfare, but can also include a broader range of topics such as regulatory, professional, and philosophical subjects. 8 Teaching and learning in AWE are particularly important for veterinary students as developing ethical skills may assist in dealing with the psychological work-related challenges veterinarians experience. 9,10 For instance, research undertaken on veterinary students at the University of Queensland Australia suggests that those students who understand and appeal to ethical norms for guidance in decision making are less likely to suffer moral distress.…”
Section: Introductionmentioning
confidence: 99%
“…7 A structured curriculum usually provides scientific evidence and ethical discussion of animal welfare, but can also include a broader range of topics such as regulatory, professional, and philosophical subjects. 8 Teaching and learning in AWE are particularly important for veterinary students as developing ethical skills may assist in dealing with the psychological work-related challenges veterinarians experience. 9,10 For instance, research undertaken on veterinary students at the University of Queensland Australia suggests that those students who understand and appeal to ethical norms for guidance in decision making are less likely to suffer moral distress.…”
Section: Introductionmentioning
confidence: 99%
“…In Magalhães-Sant'Ana's study of ethical teaching in 2014, he found that animal welfare related topics that were mentioned as part of the teaching of ethics include: the five freedoms (freedom from hunger and thirst, freedom from discomfort, freedom from pain injury or disease, freedom to express normal behaviour and freedom from fear and distress); quality of life; animal suffering; and animal pain [59].…”
Section: 23mentioning
confidence: 99%
“…Three papers discuss the training of veterinary students in the ethics of end of life issues and euthanasia, from both the United States and Europe [4,58,59]. Two papers study attitudes to euthanasia of practising veterinarians of varied age, gender, work experience and working circumstances [60,61].…”
Section: Veterinary Trainingmentioning
confidence: 99%
See 2 more Smart Citations